1989
DOI: 10.1557/jmr.1989.0911
|View full text |Cite
|
Sign up to set email alerts
|

Glass formation and glass structure of BiO1.5–CuO–Ca0.5Sr0.5O system

Abstract: The glass-forming region of the BiO1.5–CuO–Ca0.5Sr0.5O system has been determined by melting 5 g batches. Glass rods 4 mm in diameter and 75 mm long have been made. The glass transition temperatures (TG) and the onset crystallization temperatures (Tx) are around 390 °C and 440 °C, respectively. Densities of these glasses range from 5.5 to 7.0 g/cm3. The glass structure consists of the [BiO3] and [BiO6] units, and the conversion between these two polyhedra mainly depends on the Ca0.5Sr0.5O amount. The molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
3

Year Published

1991
1991
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(33 citation statements)
references
References 7 publications
0
30
0
3
Order By: Relevance
“…This is confirmed from the fact that in the present glasses, the band observed at 696-720 cm −1 in infrared spectra is assigned to B-O-B bending vibrations in [BO 3 ] triangles [39] while the strong bands in the range 1258 cm −1 and 1319 cm −1 arises from Bi-O − stretching vibrations of BiO 3 units. The band in the present IR spectra around 855 cm −1 represents the convolution of the absorbance bands reported for different bismuthate glasses at 840 cm −1 and 860 cm −1 , assigned to the total symmetric stretching vibrations of the [BiO 3 ] and [BiO 6 ] polyhedra, respectively [40,41]. In the present study this band is observed at 900 cm −1 which increases in intensity and shifts to 966 cm −1 as Bi 2 O 3 content is increased from 45 mol% to 70 mol%.…”
Section: Raman and Ir Spectramentioning
confidence: 74%
“…This is confirmed from the fact that in the present glasses, the band observed at 696-720 cm −1 in infrared spectra is assigned to B-O-B bending vibrations in [BO 3 ] triangles [39] while the strong bands in the range 1258 cm −1 and 1319 cm −1 arises from Bi-O − stretching vibrations of BiO 3 units. The band in the present IR spectra around 855 cm −1 represents the convolution of the absorbance bands reported for different bismuthate glasses at 840 cm −1 and 860 cm −1 , assigned to the total symmetric stretching vibrations of the [BiO 3 ] and [BiO 6 ] polyhedra, respectively [40,41]. In the present study this band is observed at 900 cm −1 which increases in intensity and shifts to 966 cm −1 as Bi 2 O 3 content is increased from 45 mol% to 70 mol%.…”
Section: Raman and Ir Spectramentioning
confidence: 74%
“…This is confirmed from the fact that in the present glasses, the band observed at 696-720 cm −1 in infrared spectra is assigned to B-O-B bending vibrations in [BO 3 ] triangles [24] while the strong bands in the range 1258 cm −1 and 1319 cm −1 arises from B-O − stretching vibrations of orthoborate and pyroborate in BO 3 units [25]. The IR band in around 855 cm −1 represents the convolution of the absorbance bands reported for different bismuthate glasses at 840 cm −1 and 860 cm −1 , assigned to the total symmetric stretching vibrations of the [BiO 3 ] and [BiO 6 ] polyhedra, respectively [26,27]. The infrared spectral range of 900-950 cm −1 is typical for the stretching vibrations of [BO 4 ] units [28].…”
Section: Discussionmentioning
confidence: 90%
“…The weak band at ∼520 cm −1 is due to v 4 vibration of [BO 4 ] tetrahedral [15] [20,21]. The band at ∼1270 cm −1 is due to Bi-O − stretching vibrations of [BiO 3 ] triangles [9,16,18], and the band at ∼1520 cm −1 is due to asymmetrical stretching of [BiO 3 ] triangles [18].…”
Section: High-temperature Microscopementioning
confidence: 97%